Reliability, Validity and Factor Structure of Drug Abuse Screening Test - Sayed Hadi Sayed Alitabar; Mojtaba Habibi; Maryam Falahatpisheh; Musa Arvin (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: According to the increasing of substance use in the country, more researches about this phenomenon are necessary. This Study Investigates the Validity, Reliability and Confirmatory Factor Structure of the Drug Abuse Screening test (DAST).  Materials and Methods: The Sample Consisted of 381 Patients (143 Women and 238 Men) with a Multi-Stage Cluster Sampling of Areas 2, 6 and 12 of Tehran Were Selected from Each Region, 6 Randomly Selected Drug Rehabilitation Center. The DAST Was Used as Instrument. Divergent & Convergent Validity of this Scale Was Assessed with Problems Assessment for Substance Using Psychiatric Patients (PASUPP) and Relapse Prediction Scale (RPS). Results: The DAST after the First Time Factor Structure of Using Confirmatory Factor Analysis Was Confirmed. The DAST Had a Good Internal Consistency (Cranach's Alpha, and the Reliability of the Test Within a Week, 0.9, 0.8). Also this Scale Had a Positive Correlation with Problems Assessment for Substance Using Psychiatric Patients and Relapse Prediction Scale (P<0.01). Conclusion: The Overall Results Showed that the Drug Abuse Screening Test in Iranian Society Is Valid. It Can Be Said that Self-Report Scale Tool Is Useful for Research Purposes and Addiction.